Recent Advances in Nitrogen-Containing Heterocyclic Scaffolds as Antiviral Agents - Kanupriya; Mittal, Ravi K.; Sharma, Vikram; Biswas, Tanya; Mishra, Isha (Medicinal Chemistry, 2024)
This study aims to provide a thorough analysis of nitrogen-containing heterocycles, focusing on their therapeutic implications for the development of targeted and effective antiviral drugs. To better understand how nitrogen-containing heterocycles can be used to create antiviral drugs, this review adopts a systematic literature review strategy to compile and analyze pertinent research studies. It combines information from various fields to understand better the compounds' mode of action and their therapeutic potential. This review paper summarizes data from multiple sources to highlight the promising potential of heterocycles containing nitrogen as promising possibilities for future antiviral treatments. The capacity to engage selectively and modulate critical pathways bodes well for their use in developing new viral therapies. In conclusion, nitrogen-containing heterocycles are shown to be of utmost importance in the field of medicinal chemistry, as emphasized by the review paper. It emphasizes the central importance of chemical insights and pharmacological potential in developing novel and effective antiviral medicines by bringing them together.
Keywords: pyrazole